Teachers’ Quality and Students’ Academic Performance in Osun State Public Senior Secondary Schools, Nigeria - Shittu, Afeez Adeshina (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Effective and efficient quality of teachers improves the level of students’ academic performance. This study investigated teachers’ quality and students’ academic performance in Osun State Public Senior Secondary Schools, Nigeria. The objectives of this study were to establish the relationship between teachers’ academic qualifications; teachers’ years of teaching experience; teachers’ professional qualifications and teachers’ exposure to in-service training and students’ academic performance in Osun State Public Senior Secondary Schools. The study adopted a descriptive survey of correlational type. Three hundred respondents were used for the study. Teachers’ Quality Questionnaire” (TQQ) and Students’ Academic Performance Proforma (SAPP) were used for data collection. Five research questions were raised and answered to guide the study's conduct using descriptive statistics of frequency and percentages. Five research hypotheses were formulated and tested using inferential Pearson Product-Moment correlation statistics at 0.05 significance level. Findings showed that teachers’ quality has a positive and significant relationship with students’ academic performance in Osun State Public Secondary Schools, Nigeria. Based on the findings, it was recommended among others that; school management should ensure that teachers yet to register as professionals should be encouraged to do so. This will enable teachers to register with the Teacher Registration Council of Nigeria (TRCN) and be identified as qualified teachers also endeavours to motivate teachers to attend educational conferences to improve their teaching skills to be effective and efficient.